2021
DOI: 10.3389/fphar.2021.753599
|View full text |Cite
|
Sign up to set email alerts
|

Achyranthes bidentata Polysaccharide Activates Nuclear Factor-Kappa B and Promotes Cytokine Production in J774A.1 Cells Through TLR4/MyD88 Signaling Pathway

Abstract: Achyranthes bidentata Blume, a traditional Chinese medicine, is widely acknowledged for its function of invigorating the liver and kidneys and as a stranguria-relieving diuretic and used in the treatment of edema, gonorrhea, and other diseases. Polysaccharide (ABPS), isolated from Achyranthes bidentata Blume, has been demonstrated to have multiple biological activities including immunomodulatory effects. However, the mechanisms underlying the effects of ABPS have not been fully investigated. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…TLRs have been discovered as key membrane receptors that perform an instrumental function in activating macrophages ( Fan et al, 2021 ). Among TLRs, several investigations have demonstrated that TLR4 is implicated in the generation of cytokines in response to polysaccharide stimulation ( Liu et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…TLRs have been discovered as key membrane receptors that perform an instrumental function in activating macrophages ( Fan et al, 2021 ). Among TLRs, several investigations have demonstrated that TLR4 is implicated in the generation of cytokines in response to polysaccharide stimulation ( Liu et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…ABPS alleviates OA by reducing the inflammatory response through the arachidonic acid Pathway ( 11 ). In addition, it confers bone protective effects by promoting cell proliferation and bone formation ( 10 ). In the present study, it was found that ABPS can improve cartilage ECM homeostasis, thereby alleviating articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Achyranthes bidentata has been extensively used for the treatment of OA due to its reported anti-inflammatory and antioxidant properties ( 8 , 9 ). Achyranthes bidentata polysaccharides (ABPS) is a water-soluble form of fructan that can be extracted from the Achyranthes bidentate plant ( 10 ). The chemical structure of ABPS is dominated by furan rings, where its molecular weight is in the range of 1.4-3.4 kDa ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of cytokines (IL-1β and TNF-α) can be mediated by multiple signals, among which Toll-like receptor (TLR) is the most signi cant [43]. Native polysaccharides can modulate immune cell functions in vitro by interactions with immunoreceptors, such as TLRs [44].…”
Section: Cytokine Levelmentioning
confidence: 99%